Increased plasma and erythrocyte lipid peroxidation in hyperlipidemic individuals - YALÇIN, AHMET SUHA (My University, 1989)
[No abstract available]
Keywords: Erythrocyte; Hyperlipidemia; Lipid peroxidation; Plasma